2018
DOI: 10.4049/jimmunol.1701203
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Human Neutrophil Extracellular Traps Contributes to Angiopoietin-Mediated In Vitro Proinflammatory and Proangiogenic Activities

Abstract: Neutrophil extracellular traps (NETs) are composed of nuclear DNA in a web-like structure extruded from neutrophils in response to either bacterial infection or inflammation. We previously reported the expression of angiopoietin Tie2 receptor on human neutrophils and the capacity of both angiopoietins (Ang1 and Ang2) to induce proinflammatory activities, such as synthesis and release of platelet-activating factor, upregulation of β integrin complex (CD11/CD18), and neutrophil chemotaxis. In contrast, only Ang1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 73 publications
1
43
0
Order By: Relevance
“…Glycocalyx loss is considered a key event in SM pathogenesis [48]. Angiopoietin-induced NET release may also contribute to angiopoietin-mediated endothelial activation [21] and accentuate the microvascular dysfunction due to parasite sequestration [49]. Furthermore, the increase in NETs may exacerbate intravascular thrombosis [22] and promote ischemia and reduced tissue perfusion [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycocalyx loss is considered a key event in SM pathogenesis [48]. Angiopoietin-induced NET release may also contribute to angiopoietin-mediated endothelial activation [21] and accentuate the microvascular dysfunction due to parasite sequestration [49]. Furthermore, the increase in NETs may exacerbate intravascular thrombosis [22] and promote ischemia and reduced tissue perfusion [24].…”
Section: Discussionmentioning
confidence: 99%
“…A key mechanism underlying both the pathogen-killing and pathogenic effects of neutrophils in other human infections is the release of neutrophil extracellular traps (NETs). Activated neutrophils form NETs by releasing extracellular deoxyribonucleic acid (DNA), chromatin, and granule proteins capable of capturing and destroying pathogens [20]; however, they can also exacerbate angiopoietin-mediated endothelial activation [21] and tissue damage [22, 23]. Plasmodium falciparum -infected red blood cells (RBCs) stimulate human neutrophils to release NETs in vitro [19].…”
mentioning
confidence: 99%
“…Consequently, it is possible that NETs formation in the perioperative period is triggered by direct contact with the extracorporeal circuit or with other pathways, such as complement activation, platelet activation, and endothelial cell activation. On the basis of our in vitro study, 40 in which the peak of NETs synthesis was observed within 3 hours poststimulation with proinflammatory mediators, we elected to measure circulating NETs 3 hours postprocedure. Additionally, it is possible that measuring NETs at this time point after CPB separation does not allow enough time for the triggering of NETs formation by the general inflammatory response associated with CPB.…”
Section: Discussionmentioning
confidence: 99%
“…Another 25 ml sample of venous blood was mixed with Anticoagulant Citrate Dextrose Solution USP Formula A (MP Biomedicals, Solon, OH). Neutrophils were isolated and resuspended in RPMI medium supplemented with 25 mM HEPES and 1% penicillin/streptomycin, as described previously (27). Contamination with PBMCs was ,0.1% as determined by morphological analysis and flow cytometry (data not shown), and viability was .98% (trypan blue dye exclusion) (27).…”
Section: Study Protocol: Serum and Neutrophil Collectionmentioning
confidence: 99%
“…High-sensitivity CRP (hsCRP) in serum samples was quantified by nephelometry at the biochemistry laboratory at the MHI. (27).…”
Section: Nets and Biomarkers Quantificationmentioning
confidence: 99%